A molecularly imprinted polymer on reduced graphene oxide-gold nanoparticles modified screen-printed electrode for selective determination of ferulic acid in orange peels - Buffon, Edervaldo [UNESP] (2021)
This work reports the development of a molecularly imprinted polymer used for the sensitive and selective electrochemical detection of ferulic acid. The device was prepared by the electropolymerization of molecularly imprinted poly(phenol) film on screen-printed electrode modified with reduced graphene oxide and gold nanoparticles. The modified electrode was characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy with field emission gun, energy dispersive X-ray spectroscopy, RAMAN spectroscopy and atomic force microscopy. Under optimized conditions, the proposed electrode presented a linear working range of 10 nM to 1 µM and a detection limit of 3.1 nM (n = 3). The sensor displayed good repeatability and stability over time, as well as excellent selectivity when applied for the detection of ferulic acid molecule. The method proposed here was successfully applied for ferulic acid detection in orange peels. The analyses were validated by recovery assays, where recovery values between 99 and 103% were obtained. The results of the study show that this electroanalytical methodology has good accuracy when employed for the detection of ferulic acid.